Physicians' desk reference 2015. (Montvale, NJ : PDR Network, 2014)
This reference contains FDA-approved drug label information, including warnings and precautions, drug interactions, and full-color images of some drugs. Every label includes information on dosages, side effects, and safety information, such as contraindications, pregnancy ratings, and interactions with other drugs, food, or alcohol.
Manufacturer's index -- Brand and generic name index -- Product category index -- Product identification guide -- Product information -- Dietary supplements -- Drugs that should not be used in pregnancy -- Drugs that should not be crushed.
At head of title : PDR 69 edition 2015.
Includes indexes (Manufacturer's index (1-5 p.), Brand and generic name index ([101]-121 p.), Product category index ([201]-209 p.)).
Includes bibliographical references and indexes.
Keywords: Drugs -- Dictionaries; Pharmacology -- Dictionaries; Pharmacy; Materia medica; Biological products